Do Depression and Binge Drinking Explain the Increased Risk of Sexual Violence Among Sexual Minority Middle and High School Girls? - Edwards, Katie M. (Journal of interpersonal violence, 2022)
Sexual violence (SV) occurs at rates higher among sexual minority youth than heterosexual youth, but the mechanisms explaining this higher risk are understudied. We examined if binge drinking and depression explain the higher rates of SV victimization among sexual minority middle and high school girls. Female students (N = 1,145) in Grades 7th to 10th completed a survey that assessed for SV, binge drinking, depression, sexual orientation identification, and sex at birth. Sexual minority girls had higher rates of SV victimization compared with heterosexual girls. Binge drinking and depression fully mediated the relationship between sexual orientation status and SV victimization among girls. SV prevention programming for sexual minority girls are urgently needed. Programs that seek to reduce binge drinking and depression may be especially impactful in reducing the risk of violence among sexual minority girls.